2021
DOI: 10.1007/s00357-021-09397-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Boosting and Bagging for Decision Trees of Rankings

Abstract: Decision tree learning is among the most popular and most traditional families of machine learning algorithms. While these techniques excel in being quite intuitive and interpretable, they also suffer from instability: small perturbations in the training data may result in big changes in the predictions. The so-called ensemble methods combine the output of multiple trees, which makes the decision more reliable and stable. They have been primarily applied to numeric prediction problems and to classification tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“… 4 , 5 Our strategy consisted of a two-fold approach: during the training phase, we employed boosting techniques and applied bootstrapping for rigorous testing. 31 , 32 Our results demonstrated that when analyzing tabular data, the tree-based models consistently outperformed the regression models. We assessed six different models and fine-tuned their hyperparameters through the boosting technique, leading us to identify CatBoost as the top-performing model in alignment with the findings of the study by Li et al 19 …”
Section: Discussionmentioning
confidence: 67%
“… 4 , 5 Our strategy consisted of a two-fold approach: during the training phase, we employed boosting techniques and applied bootstrapping for rigorous testing. 31 , 32 Our results demonstrated that when analyzing tabular data, the tree-based models consistently outperformed the regression models. We assessed six different models and fine-tuned their hyperparameters through the boosting technique, leading us to identify CatBoost as the top-performing model in alignment with the findings of the study by Li et al 19 …”
Section: Discussionmentioning
confidence: 67%
“…The community composition system formed by different vegetation types, hierarchical structures and functions in the forest ecosystem is the material basis of ecological service functions. Therefore, exploring the material basis of forest ecosystem service functions is of great significance for in-depth research on the material basis and evolution law of forest ecosystem service functions [6,7].…”
Section: Research On the Change Relationship Of Environmental Carryin...mentioning
confidence: 99%
“…Both RT and ERT algorithms have been tested only in the complete rankings scenario, where they obtain results that are competitive with LRT, but still inferior, in their experimentation. It is worth mentioning the approach in Plaia et al (2021, and Plaia and Sciandra (2019), which proposes using the sum of distances between rankings as the impurity criterion in conjunction with the median ranking, performing a branch and bound algorithm over rankings. However, it is focused on the problem of rankings with weighted labels, which is not directly comparable to the results of LRT on the standard problem.…”
Section: Introductionmentioning
confidence: 99%